Case Of Osteum Secondum type Atrial Septal Defect Presenting As Postpartum Pulmonary Hypertension and Heart Failure with reduced EF - Thakkar, Siddharth; Kotak, Charmi; Kumar, Sunil; Nouni, Harshita (Journal of Neonatal Surgery, 2025)
Atrial septal defect (ASD) is one of the most common congenital heart diseases in adults. In many instances, it is diagnosed during or shortly after pregnancy. A 30 -year-old female with no known past medical history presented to the OPD with atypical chest pain and shortness of breath. She reported that she had delivered her third baby 6 months prior at an outside hospital and had been experiencing symptoms since delivery. Symptoms were noted after delivery at the outside hospital and she was referred to higher hospital. In the emergency department the patient was hypoxic at 94% on room air. Electrocardiogram showed right ventricle (RV) enlargement, LV strain pattern, P-pulmonale , and . Her EKG also had notching of the QRS in the inferior leads. A 2D echocardiogram displayed a large osteum-secundum atrial septal defect measuring 3.4 cm in diameter with a bidirectional atrial shunt. She was also noted to have a severely dilated right ventricle, and moderate tricuspid valve regurgitation with pulmonary artery pressure of 40 mmHg. Her ejection fraction was 15% and thin rim of pericardial effusion is seen. Pregnancy causes specific physiologic changes that affect hemodynamics and can unmask an ASD. Firstly, hormonal changes early in pregnancy decrease blood pressure by 5-10 mmHg, leading to an increase in cardiac output. Secondly, plasma volume can increase by up to 50% through the second trimester, also increasing cardiac output. These physiologic changes can exacerbate RV overload, especially in women with RV dilation and enlargement from untreated ASDs, leading to the characteristic symptoms of heart failure described above. Our case was different because the patient did not meet the strict criteria for surgical closure. There was concern that deferring surgical correction of the ASD would result in a net right to left shunt and subsequent Eisenmenger syndrome, a feared complication of an untreated ASD. After a discussion with the patient, the decision was made to proceed with conservative management with the hope of relief in signs and symptoms of ASD. Once diagnosed, the decision to close ASD is complicated, dependent on multiple factors, and requires adequate risk/benefit analysis, patient communication, and a multi-disciplinary approach